MEDIA ONLINE DAN DISKRIMINASI RASIAL PAPUA - Safira Adnin Karlina; Nabila Kusuma Wardhani (JIKE: Jurnal Ilmu Komunikasi Efek, 2020)
The siege of Papuan student dormitories on Jalan Kalasan, Surabaya has caused controversy. The actions of the authorities in handling the case of the fall of the national flag into the gutter using tear gas were increasingly controversial when the incident was reported by the media, such as Detik.com and Tirto.id. This study aims to determine the comparison of news framing, especially the application of ideology and the political economy of the media, to approach objective and independent reporting. This study uses a qualitative approach with the Zhongdang Pan and Gerald M. Kosicki framing analysis methods. The results of the study show that Detik.com framed the news by taking sides with the authorities with a single source of news without verifying or confirming to the opposite party and using the phrase "stubborn" to make Papuan students in the guilty party and also ignore the background of the incident. While the framing of the news carried out by Tirto.id's media provides a point of view of news that does not justify the actions of the authorities handling Papuan students, and teaches why many reactionary masses outside Papua are demanding racial discrimination and persecution by mass organizations and officials. Keywords: online media, analysis, framing, Papua, racism, Pan and Kosicki.